MODERN PRACTICE OF RISK ASSESSMENT OF LOGISTICS MANAGEMENT OF ECONOMIC SECURITY OF TRANSPORT ENTERPRISES - Vivchar , O.I.; Stalinska , O.V.; Didchenko , O.I.; Kohut-Ferens , O.I.; Shatarsky, A.Y. (The actual problems of regional economy development, 2020)
A comprehensive study of risks the logistics management of economic security transport enterprises in modern conditions. It is established that the risk of logistics management of economic security transport enterprises is a set of economic, organizational and technical actions aimed at identifying types, factors and sources of risk, risk assessment, development and implementation of measures to reduce its level and prevent possible negative consequences and take into account factors the influence of the external environment – competitors, suppliers, government decisions, public opinion, market conditions, lack of full relevant information, etc. It is noted that the main functions of risk are innovative, regulatory, protective, compensatory, socio-economic and analytical. It is substantiated that risks can be determined by quantitative and qualitative analysis (minimax rule (Savage criterion; Hurwitz rule). It is proved that the system of indicators quantitative risk assessment in the system of economic security covers absolute values (variance, standard deviation, semi-variation, seven-square deviation), relative (probability, coefficient of variation, risk factor). A comprehensive study of risk factor the logistics management of economic security transport enterprises has been formed. The main methods of regulating the degree of risk transport enterprises are identified: risk avoidance; risk compensation; prognostication; monitoring; risk retention; creation of special reserve funds; involvement of external sources; risk transfer; hedging; risk reduction. On the basis of which it is proved that the purpose of reducing the risks of economic security of transport enterprises can be considered a comprehensive response to potential and real threats, as well as ensuring a high potential for development of transport enterprises in the future.